DEVELOPMENT OF STUDENTS' ABILITY TO ENGAGE IN GROUP ACTIVITIES IN TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2024)
In this article, attention is paid to the organization of technology classes and the development of students' creative abilities during the classes.